Application of artificial intelligence technology in monitoring students’ health: Preliminary results of Syiah Kuala Integrated Medical Monitoring (SKIMM) - Pratama, Rovy; Suhanda, Rachmad; Aini, Zahratul; Nurjannah, Nurjannah; Geumpana, Teuku A. (Narra Sains Indonesia, 2024)
Health promoting university is a holistic approach to health that uses higher education settings to create a learning environment that improves the health and well-being of the campus community in a sustainable manner. The utilization of technology such as artificial intelligence (AI) could be one of the main success factors in the implementation of health-promoting universities to increase the effectiveness and efficiency of all stages of activities carried out in health promotion and prevention efforts. Integrated monitoring with the utilization of AI in this program is conducted to evaluate the health status of the students. The Syiah Kuala Integrated Medical Monitoring (SKIMM) has three components of continuous health status evaluation: vital signs, nutritional status, and burnout status. Health status monitoring was conducted continuously for three months among medical students at the Faculty of Medicine Universitas Syiah Kuala, Banda Aceh, Indonesia. This system uses the WhatsApp application as a platform to monitor health status. Student health monitoring in this program consists of two main activities: the health measurement phase and the health monitoring phase. The use of the SKIMM system to monitor students' vital signs, nutritional status and burnout status through the use of AI significantly raises students' awareness to conduct timely self-examination and enables sustainable healthy lifestyle behavior change. The adoption of AI technology allows for continuous health promotion to the entire academic community, including students in implementing the health promoting university.